Lomonosov Moscow State University: the major centre for Russian research and education into tourism and recreation - Aleksandrowa, Anna; Aigina, Ekaterina (Turyzm/Tourism, 2013)
The author discusses the tourism geography research which has been undertaken at Lomonosov State University in Moscow over many years. This academic institution is one of the most famous research centres dealing with spatial recreation systems. At first (from the 1960’s), research was mainly on geographical and technical issues, but the research area was gradually enlarged for example to include social and humanistic elements. The best known research has been done on ‘spatial recreation systems’, ‘polarized landscapes’, the ‘recreational economy spatial complex’, and the ‘environmental model of a spatial system’.